Testing for Caribbean content in the CXC geography programme - Griffith, Anthony D.
This paper assesses the Caribbean Examinations Council (CXC) examination process in geography against one of the stated aims of the CXC geography syllabus, which is that, through the study of geography, students are expected to acquire knowledge, understanding, and appreciation for the physical environment and the social conditions and problems of their own territory, as well as those of other Caribbean territories. It presents a table based on a content analysis of the CXC geography examination papers (General Proficiency) over the five-year period, 1987-1991. From examination of the data, a number of preliminary conclusions are presented for consideration
Keywords: CXC examinations